P117 3D cryo-electron microscopic analysis of the disease mechanism of α1-antitrypsin deficiency. (2nd December 2011) - Gooptu, B; Chaban, Y; Irving, J A; Clare, D K; Lomas, D A; Orlova, E; Saibil, H R
Abstract : α1 -antitrypsin deficiency is characterised by predispositions to liver disease and severe, early-onset emphysema. It is caused by point mutations that destabilise the molecular structure of α1 -antitrypsin, leading it to self-associate into chains known as polymers. Polymerisation abolishes the antiprotease activity of α1 -antitrypsin and causes circulating deficiency of the protein. These loss-of-function effects result in dysregulated elastase activity within the lung parenchyma. In addition, polymerisation has pro-inflammatory gain-of-function effects that must be mediated through the structural characteristics of the polymer itself. It is therefore important to understand the structure of the α1 -antitrypsin polymer to identify targets for drug design. We have used cryo-electron microscopy, single particle reconstruction techniques to study α1 -antitrypsin polymers. Analysis of the 3D arrangement of α1 -antitrypsin molecules within the directly observed polymer chain allows us to evaluate current competing models of polymer assembly.